(untitled) (Rome, 2001)
This book is a comprehensive, up-datable diagnostic guide for the pathogens and diseases listed in the NACA/FAO/OIE Quarterly Aquatic Animal Diseases reporting system including a number of other diseases which are significant in the Asia region.
Keywords: Animals diseases,Aquaculture,Aquatic animal diseases